Young lung cancer: from diagnosis to survivorship - Florez, Narjust; Kiel, Lauren; Kaufman, Rebekah; LoPiccolo, Jaclyn; Ricciuti, Biagio; Morabito, Angela; Fakorede, Olayinka; Mantz, Courtney; Olazagasti, Coral; Swami, Nishwant; Kanan, Duaa; Alder, Laura; et al. (Frontiers in Oncology, 2025)
BackgroundYoung patients with lung cancer represent a distinct population, with unique disease and treatment-related characteristics, as well as psychosocial and survivorship needs. Nevertheless, this population remains vastly understudied.MethodsWe review the unique clinicopathological characteristics and needs of young patients with lung cancer, including topics such as incidence rates, diagnostic challenges, genomics, treatment patterns and outcomes, psychosocial needs, fertility and sexual health, and palliative care. We discuss emerging and understudied data, provide recommendations on aspects in which future research is warranted, and advocate for actionable strategies that multi-disciplinary healthcare teams may adopt to provide more personalized and equitable care.ResultsThough epidemiological trends suggest an overall decrease in lung cancer incidence among all age groups, recent increasing incidences have been reported among certain young populations in the U.S., as well as among Hispanic women and women in certain European countries. Young patients are significantly more likely to be female or Asian/Pacific Islander, have no tobacco use history, metastasis to the brain, and a higher frequency of somatic mutations or rearrangements. Diagnostic delays pose a considerable concern to young patients with lung cancer and may contribute to how these patients are more likely to be diagnosed with advanced disease than their older counterparts. However, young patients demonstrate improved survival compared to older patients, underscoring the importance of survivorship care. Young patients are more likely to be diagnosed at a disruptive time in their lives, rendering them with distinct psychosocial needs and financial toxicity. Future data on treatment-related effects on fertility and sexual health for young patients is warranted, as is the data related to complementary medicine use. Training in palliative care and promoting a positive attitude towards supportive care is also essential.ConclusionsYoung patients with lung cancer represent a distinct patient population, necessitating disease management that is markedly different from that of older patients with lung cancer. Future research, some of which are highlighted by this Review, will aid in elucidating risk factors, survival rates, and clinical, genomic, and histopathological characteristics of young-onset lung cancer to improve screening, early detection, prevention, and treatment of this understudied population.